APLIKASI SISTEM AKUNTANSI PERSEDIAAN BARANG DAGANG MENGGUNAKAN METODE RATA-RATA BERGERAK ( STUDI KASUS : TOKO INTI MAS MEUBEUL CIREBON ) - Lena Magdalena; Aprilia Aprilia; Amroni Amroni (Jurnal Digit, 2018)
Abstract Toko Inti Mas Meubel Cirebon is a store that sells furniture such as couch, bupet, and others. Toko Inti Mas Meubel Cirebon, the management of transaction data on accounting activity and report making such as reports of sales, purchases, and inventory of merchandise are still manual. Therefore it is necessary to create an application in the form of a special program that can manage well the data purchase, sales, and inventory. The research method used in this study is a descriptive case study method, the steps being taken are observation and interview. Input data required for further analysis and system design using flowchart tools, context diagram, Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD). The programming language used is Microsoft Visual Basic 6.0, while using Microsoft Access database 2010. The result of this research is a special program application in the form of Accounting Information System which consists of functions to handle the procedures that are procedure of buying, selling and inventory of merchandise. From the results of implementation and testing can be concluded that the application has been made can be applied to Toko Inti Mas Meubel Cirebon. Keywords : Accounting, Inventory, HPP, Moving Average